2008
DOI: 10.1124/dmd.107.020131
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Modeling of Nonspecific Binding to Human Liver Microsomes

Abstract: ABSTRACT:Estimation of unbound fraction of substrate in microsomal incubation media is important in accurately predicting hepatic intrinsic clearance and drug-drug interactions. In this study, the unbound fraction of 1223 drug-like molecules in human liver microsomal incubation media has been determined using equilibrium dialysis. These compounds, which include 27 marketed drug molecules, cover a much broader range of physiochemical properties such as hydrophobicity, molecular weight, ionization state, and deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 18 publications
1
50
0
Order By: Relevance
“…The ADME assays were performed via reported methods as described previously for MDCK P app (14), MDR-MDCK P-gp (14), and metabolic stability (14,15,22,35).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ADME assays were performed via reported methods as described previously for MDCK P app (14), MDR-MDCK P-gp (14), and metabolic stability (14,15,22,35).…”
Section: Data Collectionmentioning
confidence: 99%
“…Metabolic stability data for the drugs and the candidates, expressed as unbound intrinsic clearance (CL int,u ), was generated using a HT in vitro human liver microsome (HLM) assay and an in silico model of estimated microsomal free fraction (cF u,mic ) according to eq 2 (22). The use of CL int,u has been found to give a more accurate prediction of in vivo clearance than does CL int,app and as such we have used this value for these analyses (23).…”
Section: P-gp Er ¼mentioning
confidence: 99%
“…b Fraction unbound estimates in rat plasma and rat liver microsomes were obtained using in silico models developed at Pfizer as described previously with human liver microsomes (Gao et al, 2008). Literature free fraction of indomethacin in rat plasma is 0.040 (Dawidowicz et al, 2008), indicating high confidence in the in silico predictions.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, indomethacin and the glycine amide 4, which contained free carboxylic acid substituents, were completely resistant to metabolism in liver microsomes from both species. Considering that microsomal unbound fractions of amides 1, 2, and 3 predicted from in silico computational models (Gao et al, 2008) were comparable (Table 1), the free intrinsic clearance values (amide 1: 6646 ml/min/kg; amide 2: 2034 ml/min/kg; and amide 3: 772 ml/min/kg) obtained from scale-up of half-life data (normalized for nonspecific microsomal binding) (Obach, 1999), suggested that the strategy of attenuating metabolism via structural modification of the amide substituent in 1 had worked in our favor. Of much interest in this endeavor were the observations on the similarity in metabolic stability and free microsomal fraction of indomethacin and glycine amide 4 that resulted in comparable intrinsic clearance predictions of Ͻ10 ml/min/kg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation